Minor salivary gland biopsy in Sjögren’s syndrome: A review and introduction of a new tool to ease the procedure - Varela-Centelles, Pablo (Medicina Oral S.L., 2014)
Objectives: To review the existing techniques for minor salivary gland biopsy (MSGB) in the lip and to suggest a new approach to ease the procedure and reduce post-operative complications. Study Design: A comprehensive literature review and a descriptive study of a new surgical technique. Results: Diverse incisions have been suggested for MSGB with different designs (ellipse, circular, linear), different directions (parallel, oblique, vertical) and a wide range of lengths (from 1 mm up to 3 cm), but no comparative studies supporting the advantages of a particular type of incision over the others could be retrieved. A variety of features of the existing techniques for MSGB are linked to undesired events and surgical complications which could be minimized by modifying certain aspects of these procedures. The technique described, together with the use of the S forceps, represents a significant improvement over the already described chalazion forceps because it allows for a better access and positioning of the lower lip, improves the ergonomic conditions of the assistant, and facilitates the identification of lip areas with more superficial gland lobules. Conclusions: The suggested approach for lip MSGB includes a specifically designed instrument whose performance during lip biopsy may contribute to minimize post-operative complications. Key words:Sjögren’s syndrome, diagnosis, minor salivary gland biopsy, surgical technique, lower lip.